2012
DOI: 10.1111/j.2041-1014.2012.00639.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor‐α and interleukin‐1β expression pathway induced by Streptococcus mutans in macrophage cell line RAW 264.7

Abstract: Streptococcus mutans, a major etiological agent of dental caries, frequently causes systemic disease, such as subacute bacterial endocarditis, if it enters the bloodstream. In this study, the production pathways of the proinflammatory cytokines, tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β), induced by S. mutans in mouse macrophage were examined using a quantitative real-time polymerase chain reaction and an enzyme-linked immunosorbent assay. The S. mutans stimulated the expression of TNF-α and IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…It has been reported that TNF-α, IL-1β and keratinocyte chemoattractant (a functional homologue of human IL-8) cytokines are the distinctive biomarkers for fatal bacteremic conditions [33]. It has also been reported that S. mutans is capable of inducing TNF-α and IL-1β pathways [37]. The LFKO −/− mice with hLF supplementation decreased the expression of such cytokines suggestive of immunomodulatory role of LF.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that TNF-α, IL-1β and keratinocyte chemoattractant (a functional homologue of human IL-8) cytokines are the distinctive biomarkers for fatal bacteremic conditions [33]. It has also been reported that S. mutans is capable of inducing TNF-α and IL-1β pathways [37]. The LFKO −/− mice with hLF supplementation decreased the expression of such cytokines suggestive of immunomodulatory role of LF.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike many innate immune pathways, stimulation of a functional inflammasome requires two events, priming and activation. During priming (step 1), activation of the transcription factor NF-κB downstream of the stimulation of many PRRs, facilitates the transcription and translation of many inflammasome components (as well as the secretion of pro-inflammatory cytokines such as TNF and IL-6) [31]. Activation of the inflammasome complex (step 2) requires the exposure of cells to a separate set of PAMPs and DAMPs, which work through unique signaling pathways to induce the oligomerization of one of several different Nucleotide Oligomerization Domain (NOD)-Like Receptor (NLR) proteins, the adaptor protein Apoptosis-associated Speck-like protein containing a CARD (ASC), and pro-caspase-1, into an organized inflammasome complex [32].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike many innate immune pathways, stimulation of a functional inflammasome requires two steps. During priming (step 1), activation of the transcription factor NF-κB, downstream of the stimulation of many PRRs, leads to the production of several components of the inflammasome and the secretion of the pro-inflammatory cytokine TNF (2). Activation of the inflammasome (step 2) requires the exposure of cells to a separate set of PAMPs and DAMPs, which work through unique signaling pathways leading to the oligomerization of one of several different Nucleotide Oligomerization Domain (NOD)-Like Receptor (NLR) proteins, the adaptor protein Apoptosis-associated Speck-like protein containing a CARD (ASC), and pro-caspase-1 into an organized inflammasome complex (3).…”
Section: Introductionmentioning
confidence: 99%